Ανάλυση έως...

Click here to load reader

  • date post

    14-Apr-2017
  • Category

    Education

  • view

    29.646
  • download

    0

Embed Size (px)

Transcript of Ανάλυση έως...

  • www.mathjazz.com

    www.mathjazz.com1

    1. . 2. ()

    . 3. ()

    .

    .

    1.

    {0, 1, 2, 3, ...}= .

    {..., 3, 2, 1,0,1,2,3, ...}= .

    , ,

    0 . .

    , , / , 0

    =

    .

    , 5 , e, , 3 7 ,

    52 10+ ... . , , {x= / x }=-.

    =.

    , .

    x x

    e 3

    5 4 3 2 1 0 1 2 3 5 4

    , , : .

    {0} , {0} , {0} {0} *, *, * * .

    !

    Tom RaikHighlight , , . , , .

    Tom RaikHighlight . .

    Tom RaikHighlight . , -1 +1 . (: =2, ) (: =2+1 =2-1, )

    Tom RaikHighlight ( ) . .

    Tom RaikHighlight

    Tom RaikHighlight

    Tom RaikHighlight

  • www.mathjazz.com

    www.mathjazz.com2

    a

    a

    a

    a

    !

    2.

    , < , , :

    (, )={x/

  • www.mathjazz.com

    www.mathjazz.com3

    i. : 1 11 1 0x x

    1 x 0x

    2 21 x x 0 x x(x 1) 0x

    x 0 x 0 < x 1 . A ( ,0) [1, )= + .

    ii. : 1 12 1 1 2 1x x < < < 11 3

    x < < ,

    11 x3

    > > . 1B , 13

    =

    .

    1 :

    1A x / 2x

    =

    .

    2 :

    1A x / 4 3x 1

    = >

    .

    3 :

    1A x /1 2x

    = <

    .

    4 :

    1A x /2 4 5x 1

    =

  • www.mathjazz.com

    www.mathjazz.com4

    1

    1.

    R.

    2. R .

    3. () y ( x).

    4. .

    5. 1 2f (x ),f (x ) A 1 2f (f (x )) f (f (x ))=

    6. : : A {x= : f (x)} .

    : y : / y f (x) x

    f (A) x A

    =

    =

    :

    7. .

    8. .

    9. f,g .

    10. f .

    .

  • www.mathjazz.com

    www.mathjazz.com5

    . . () f, x A , , y, x ( y ), , x . y f x f (x) , y f (x)= .

    , : f : A x f (x) y f (x)= , x A . 1 1 2x ,x 1 2x x= 1 2f (x ) f (x )= 2 ( 1) 1 2x ,x 1 2f (x ) f (x ) 1 2x x . f : A . 1 2f (x ),f (x ) A =1 2f (x ) f (x ) 1 2f (f (x )) f (f (x ))= .

    x, . y, f x, .

    Tom RaikHighlight .

    Tom RaikHighlight y f(x) , x f.

    Tom RaikHighlight , , . . . 1-1 .

    Tom RaikHighlight , . . . 1-1 .

    Tom RaikHighlight f(f(x)) f(x)

    Tom RaikHighlight x f

    Tom RaikHighlight ,

  • www.mathjazz.com

    www.mathjazz.com6

    f, :

    ( ), f (x) ( f), x . f f(A) , x A f (x) x.

    (x,f (x)) .

    (domain) f fD fA .

    f (x) , x, f (x) , :

    fD {x= : f (x)} .

    f () x A , (range) f f (A) .

    y : y f (x) xf (A) .

    x A =

    =

    :

    f : A :

    fD ( ).

    f x, y f (x)= x x g(y)= , x y.

    fx D , fg(y) D , ff (D ) .

    f

    f (A) A

    Tom RaikHighlight

    Tom RaikHighlight , .

    Tom RaikHighlight

    Tom RaikHighlight

    Tom RaikHighlight

    Tom RaikHighlight , f

  • www.mathjazz.com

    www.mathjazz.com7

    x

    y

    A B

    O x

    y

    Cf

    O x

    y

    C

    !

    f , . f (B) f x B .

    { }f (B) y : y f (x) x x B= =

    .

    f ,g . x A , :

    f g= :

    x A f (x) g(x)= . f, g , . x f (x) g(x)= , f g . f ,g f gA , A , f gA A , .

    f Oxy . f (x, f(x)) . M(x,y) y f (x)= , M(x, f (x)) , x A , f fC .

    , y f (x)=

    fC . , y f (x)= f.

    x A y, f . :

    f

    .

    y x

    f f (A) A

    Tom RaikHighlight1. ' .2. ' .3. .

    Tom RaikHighlight . (x,y) y=f(x) (x,y) y=f(x) .

    Tom RaikHighlight

  • www.mathjazz.com

    www.mathjazz.com8

    . :

    x y,

    , ! 1 ! x y 2

    -2x , x 0

    f (x)3 x , x 0

    =

    .

    f x 0 . x 0= f (0) . x=0 f (0) 2 0 0= = .

    x=0 f (0) 3 0 0= = . f fA = . 3

    2

    2 2

    3x 1, x 2 2f (x)

    x 1, 3 x + +

    = + +

    .

    ! : 1.

    . 2. . 3. . :

    x, 2 23 2 2 + > + 2 1 0 <

    ( 1,1) Z 0 = , 23x 1 x 2

    f (x)x 1 x 3

    + = +

    ,

    . x y,

    2 23 2 2 + = + x y. 2 23 2 2 + = + 2 1 = 1 = 1 = .

    1 = 23x 1 x 5

    f (x)x 1 x 5

    + = +

    . x 5=

    f (5) 16= f (5) 26=

    1 = 23x 1 x 3

    f (x)x 1 x 3

    + = +

    . x 3=

    f (3) 10= f (3) 10= , 1 = .

    Tom RaikHighlight . .

    Tom RaikHighlight .

  • www.mathjazz.com

    www.mathjazz.com9

    2 ; Q(x, y)=0 , x, y . x , y y f (x)= . y f(x) , , , x, , x . 4 3x y 10+ = , x,y . . x . . x, . ! x y, : 1 2x , x A 1 2y y , 1 2x x ,

    1 2x , x A 1 2x x= , 1 2y y= .

    3 3x y 10 y 10 x+ = = , x,y . . x y 3y (10 x) x, x ( , ) + . . 1 2x ,x ( , ) + 1 2y ,y :

    3 31 2 1 2y y y y 1 210 x 10 x 1 2x x , f

    . 3y 10 x= , x 10> y 0< , x 10 y 0 , :

    3

    3

    x 10 x 10f (x)

    1 x x 10

    >=

    .

    5 2x y 10+ = , x, y x y. . x . . . ! x y, xA 1 2y , y . .

    Tom RaikHighlight x y

    Tom RaikHighlight ,

  • www.mathjazz.com

    www.mathjazz.com10

    2 2x y 10 y 10 x+ = = , x,y . . x y 2y 0 y 10 x 0 x 10 , x ( ,10] , A ( ,10]= .

    . xA y.

    2y 10 x= 10 x

    y

    10 x

    =

    , x ( , 10]

    y, . : 1 2x ,x A 1y 3= , 2y 3= , : 1 2y y .

    2 21 2y y 9= = 1 210 x 10 x = 1 2x x 1= = , 3 f :

    fC , f fC , x x ' .

    f y f (x)= , x, f (x) , : fD {x= : f (x)}.

    !!!

    , 1 11 1 0f (x) x x ... x

    = + + + + ,

    * , . , ( ).

    Cf

    O

    y

    x

    Tom RaikHighlight

    Tom RaikHighlight

  • www.mathjazz.com

    www.mathjazz.com11

    ,

    , g(x)f (x)h(x)

    = .

    { }f g hD x /x D D h(x) 0= .

    , , f (x) g(x)= , {0,1} - 2 .

    { }f gD x /x D g(x) 0 = R . ,

    , f (x) lng(x)= . { }f gD x /x D g(x) 0 = > .

    ( )h(x)f (x) g(x)= , 1,

    ( )h(x) h(x) lng(x)f (x) g(x) e = = .

    { }f g hD x /x D D g(x) 0 g(x) 1= > , 1. g(x)>0, :

    { }f g hD x /x D D g(x) 0 = >

    , ,

    ( )f (x) g(x)= ( )f (x) g(x)= . { }f gD x /x D= R . x x x.

    ,

    2

    + , , ( )f (x) g(x)= .

    f gD x /x D g(x) 2 = +

    x x x2

    + .

    Tom RaikHighlight

    Tom RaikHighlight

    Tom RaikHighlight

  • www.mathjazz.com

    www.mathjazz.com12

    , , ,

    ( )f (x) g(x)= . { }f gD x /x D g(x) = x x x .

    2x x + + , 0 , :

    0 > , :

    1x 2

    =

    , 2x 2 +

    =

    :

    x , 1x x<

    2x x> , x , 1 2x x x< < .

    0 = , 0x 2

    =

    :

    x x2

    ,

    x2

    =

    .

    0 < : x .

    6

    :

    . 2x 3x 2f (x)

    x +

    = ,

    . 2

    2

    x x 6g(x)x 1

    + +=

    .

    . H